Analisa Carrier To Noise Jaringan RRI pada Rute Palembang - Musi Banyuasin - Novrianda, Rahmat (Teknomatika, 2017)
Radio network technology Republic of Indonesia has been using satellite communication system, where with this wireless access system can reach difficult place reachable. This research will examine the network on the LPP-RRI that discusses the performance of radio, radio weaknesses and the advantages of this technology. In this reserch, the authors first understand the shape and configuration of RRI network on the route Palembang - Banyuasin. After that, the authors perform mathematical calculations to obtain the value of Carrier To Noise (C / N) total by calculating the value of Carrier to Noise uplink at the earth station in the city of Palembang, Carrier to Noise intermod on a satellite carrier to noise downlink ground station located in Banyuasin. After getting the value of (C / N) total subsequent authors compared the results of mathematical calculations (C / N) in total with the existing data on RRI software that can analyze the cause of the difference of both values and can provide remedies that keoptimalan better network utilization. Then, to determine the level of RRI network performance, the author must seek Eb/No and BER values for comparing the calculation results with Digital Voice standarisai with a value of 6.5 dB at BER of 10-3 where the value is expressed in network performance in good condition.Keywords : RRI, Satellites, Carrier to Noise (C / N), Eb / No, BER (Bit Error Rate)